2(3x-1)=9-(4x-1)

Simple and best practice solution for 2(3x-1)=9-(4x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-1)=9-(4x-1) equation:



2(3x-1)=9-(4x-1)
We move all terms to the left:
2(3x-1)-(9-(4x-1))=0
We multiply parentheses
6x-(9-(4x-1))-2=0
We calculate terms in parentheses: -(9-(4x-1)), so:
9-(4x-1)
determiningTheFunctionDomain -(4x-1)+9
We get rid of parentheses
-4x+1+9
We add all the numbers together, and all the variables
-4x+10
Back to the equation:
-(-4x+10)
We get rid of parentheses
6x+4x-10-2=0
We add all the numbers together, and all the variables
10x-12=0
We move all terms containing x to the left, all other terms to the right
10x=12
x=12/10
x=1+1/5

See similar equations:

| 4x(2)-8=9 | | 11x-32=32x-11 | | 2(3d-7)=6d-14 | | 3d=4d+8 | | 55x-3(9x=12)=-64 | | 12k-20=15k-38 | | 4j-6=5j | | 1+11g=14+12g | | 25-3/7f=10+4/7f | | 4(x-3))=4x-12 | | 2.3=p=0.6 | | 2(3-4)+y=5 | | 5d+2=16-2d | | -8j+14=-2(4j)-7) | | 3x+2=3(-3 | | 2-3x/4=3x+1/2 | | 6.6x-15.3=30.9 | | 27=5f−-2 | | -2/5n=-8 | | 13(x-3)^2=832 | | 0=32+32t-16t^2 | | 18=3+4(-3)-2x | | 4(f-2)=f-5+3f | | -14-v/9=-1/ | | 7=3x-23 | | 8.5x-1.3=15.7 | | 8−13=​9​​r​​+8 | | -3-7y=-10 | | 9+m=107 | | 3/5x+1=2/5x | | (X+8)/(5x-2)=3/8 | | 14x+126=10x+60 |

Equations solver categories